Successful treatment of massive biventricular thrombi associated with myocarditis: a case report - Liang, Chunshui; Liu, Hong; Cao, Zhezhe; Li, Tianbo; Wang, Yong; Xiao, Yingbin; Ma, Ruiyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMassive biventricular thrombi associated with myocarditis are rare and pose significant management challenges.Case presentationA 24-year-old male from a plateau region presented with dyspnea, chest pain, and cerebral infarction/hemorrhage. Imaging revealed giant biventricular thrombi (left: 81 × 62 × 59 mm; right: 59 × 16 mm) and LVEF of 25%.ManagementMultidisciplinary therapy included anticoagulation and GDMT.OutcomesComplete thrombus resolution occurred by 10 weeks, with improved cardiac function (LVEF 48%) and no recurrent embolism.ConclusionDrug therapy may be effective for massive biventricular thrombi in myocarditis.